Beyond 2020: Collecting Time Capsules in a Year of Pandemic. Issue 4 (4th January 2022) - Clulow, Adam; Berry, Daina Ramey
Abstract: 2020 saw a perfect storm of events. It began with the COVID-19 pandemic that swept across the globe, followed by waves of racial unrest, economic distress, and political turbulence even as wildfires, hurricanes and tropical storms tore across our region. It was clear to all of us that we were living through sweeping historical change compressed into a short space of time. This article describes the creation of Beyond 2020: Living History, a public history project at the University of Texas at Austin that aimed to respond to the events of the year. It charts the development of the project and how it came to diverge from its original design in productive ways underpinned not by an attempt to impose order or build hierarchy, the traditional tools of historical analysis, but rather by a willingness to relinquish control to create a shared space for our university community.